Consumer Attitude Toward Product Placement: A Descriptive Study Between Bangladeshi & Indian Media Program - Anima Karmakar; Md. Nur-Al-Ahad; Tanvir Hyder (Business Ethics and Leadership, 2021)
The aim of this study is to investigate Bangladeshi viewers’ attitudes towards product placement activities. Here product placement indicates a paid form of non-traditional advertisement where products or brand names are intentionally present along with the programs. Consumers’ purchase decisions relate to how they know the brand name, and traditional marketing activities failed several times to hit the customer’s black box. People are fascinated by an innovative way of product representation, a tough and challenging task for marketers. Embedded marketing or Product placement helps both viewers and marketers to build a bridge for communication. In Bangladesh, people are less conscious about their local products as well as their media programs. Media and marketing relate inextricably with each other. The study has been conducted in two aspects to investigate the consumer attitude towards product placement. The first one is a comparative analysis of several product placements between Bangladeshi and the Indian media program. The second one is devolving and analyzing questionnaires to determine the Bangladeshi viewers’ scenario about embedded marketing. The logic behind choosing the Indian tv program for comparison is that Bangladeshi viewers are habituated with the Indian program. From 121 respondents, this study tries to forecast the viewers’ attitude toward product placement. Comparing Bangladeshi and Indian movies, dramas, and reality shows, the study expresses that Bangladeshi channel set minimal concern about embedded marketing. An online survey portrays a viewer’s preference level and thinking pattern about their media programs. Proper representation of programs such as an exciting story from movies and drama, a reality show with more customer engagement, less repetition of the same news, more consciousness about irrelevant talk shows, proper timing of the advertisement can help to back the viewers to their media that allows marketers to communicate with their target customers. This study has been conducted with limited sample size. Further research may be conducted about this study with large sample size and may compare with other countries.